Local Wireless File Sharing with Live Share and Browse with Social Network with File Replication Using Structured P2P Approach in MANNET - V., Sivabala Sarathi; Amudha, S. (Indian Journal of Computer Science, 2016)
Smart file sharing is the software used to share files between the two or many devices. Wireless file sharing with current wireless sharing approaches lack in giving sufficient features to users who frequently share files, so it cannot satisfy both senders and receivers. Sharing process between cross platform might not result in good performance due to device constraints or result in poor user experience due to various Operating System versions and hardware configurations in low end wireless Smart Phones. Security is a major risk with live sharing feature. In order to avoid hacking of files by unauthorized users this software method will make the user place a file to transfer one time and many users can have access to it from their mobile device so that sender need notsend the same file to multiple users. This system acts like a temporary cloud (or) like a buffet system. This file sharing is mainly focused on media files sharing through Wi-Fi Bluetooth in wireless device like smart phone devices. This software will learn the environment of each data which needs to be shared and will decide what should be sent and what should be authenticated, and who can access a particular file. This software will notify each transaction for getting it verified by senders. The most important new feature is that receivers can browse the files in sender's devices from their own devices using Live Sharing feature to select whatthey need. This process of file sharing is applicable for sharing file with enterprises corporate industries, social network communities etc.